(3JbQjH GdeCehd aj JQJjH GdfRhds - (3HQgGf GdOjf CHh ESMGb EHQGgje Hf YeQ Hf EHQGgje Hf Ndjd GdLYHQj,J (B732 (3g` s
(3ChdgG (B:s
(3ecjgG SJ KeGfhf EYJdJ fXeJ Ydi hab GdfRhd def JdG s
(3BNQgG (B:s
(3Ef GdPi aQV CfJei LMajkG hgh GdPi ca GdMjHi GfLdkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3efXheI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B14s
Keywords: (3GdbQGAGJ hGdJLhjOs